Lessons Learned From Deploying a Code Review Analytics Platform - Bird, Christian; Carnahan, Trevor; Greiler, Michaela (Microsoft Research, 2015)
Tool based code review is growing in popularity and has become a standard part of the development process at Microsoft. Adoption of these tools make it possible to mine data from code reviews and provide access to it. In this paper, we present an experience report for CodeFlow Analytics, a system that collects code review data, generates metrics from this data, and provides a number of ways for development teams to access the metrics and data. We discuss the design, design decisions and challenges that we encountered when building CodeFlow Analytics. We contacted teams that used CodeFlow Analytics over the past two years and discuss what prompted them to use CodeFlow Analytics, how they have used it, and what the impact has been. Further, we survey research that has been enabled by using the CodeFlow Analytics platform. We provide series of lessons learned from this experience to help others embarking on a task of building an analytics platform in an enterprise setting.